PUBLIC ATTENTION AND FINANCIAL INFORMATION AS DETERMINANTS OF FIRMS PERFORMANCE IN THE TELECOMMUNICATION SECTOR - Ridwan Nurazi; Berto Usman (University of Merdeka Malang, 2015)
The remarkable progress of information technology had driven every firm to publish their financial performance by using internet. This circumstance resulted in the high public attention in order to generate the stock return. In addition, financial information such as financial ratio namely DER, LEV, NPM, ROI, and ROE were supposed to influence the firm’s performance either in positive or negative effects. This study focused on the investigation of public attention (PA) and financial information as determinants of financial performance on four companies in Telecommunication sector, Indonesia Stock Exchange (IDX), within time period from 2007 to 2012. Hereby, we pointed out that public attention and financial information considerably contribute to firm performance, in which the Pooled Least Square (EGLS) with cross section and period weight was employed. The results showed that Public Attention (PA) positively contributed towards stock return. Further, financial ratio such as debt-to-equity ratio (DER) negatively influenced the return. Leverage (LEV), net profit margin (NPM) and return on investment (ROI) positively related to return. However, return on equity (ROE) showed the contrary sign, in which it negatively influenced the return but was statistically insignificant. Then, we reported that the stock price (LNSP) did not significantly contribute towards return (RET).